The Influence of Antecedent Dimensions of Service Quality on Customer Satisfaction Towards Customer Loyalty - Bryanviko, Mayrichael; Meitiana, Meitiana; Kristinae, Vivy; Karuehni, Ina (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to determine the effect of antecedent dimensions of service quality on customer satisfaction towards customer loyalty at Perumdam Maruang Duhung. The population in this study were customers of Perumdam Maruang Duhung. The sample determination was carried out by multiplying the number of indicators by 5 and obtaining a sample of 80 respondents. The method of data collection was through surveys and distributing questionnaires to consumers as respondents for 1 week. The data analysis technique used was Structural Equation Modeling (SEM) Analysis with Partial Least Square (PLS). The results showed that the variables of Physical Evidence, Responsiveness, Assurance, Reliability, and Empathy had a positive and significant effect on Customer Satisfaction. Customer Satisfaction had a positive and significant effect on customer loyalty.